Threat vector - Clancy, Tom; Greaney, Mark (Berkley Publishing, 2012)
For President Jack Ryan, his son Jack Ryan, Jr., and the covert organization known as The Campus, the fight against America's enemies is never over. But the danger has just hit home in a way they never expected in this #1 New York Times bestselling Tom Clancy thriller.... The Campus has been discovered. And whoever knows they exist knows they can be destroyed. Meanwhile, President Jack Ryan has been swept back into the Oval Office-and his wisdom and courage are needed more desperately than ever. Internal political and economic strife has pushed the leadership of China to the edge of disaster. And those who wish to consolidate their power are using the opportunity to strike at long-desired Taiwan, as well as the Americans who have protected the tiny nation. Now, as two of the world's superpowers move ever closer to a final confrontation, President Ryan must use the only wild card he has left-The Campus. But with their existence about to be revealed, they might not even have a chance to enter the battle before the world is consumed by war.